Impact motion control of a flexible dual-arm space robot for capturing a spinning object. (19th June 2019) - Li, Xiali; Wu, Licheng
As an autonomous vehicle that moves on the space orbit, a space robot needs to be carefully treated on the motion planning and control method. In this article, the optimal impact and postimpact motion control of a flexible dual-arm space robot capturing a spinning object are considered. Firstly, the dynamic model of the robot systems is built by using Lagrangian formulation. The flexible links are modeled as Euler–Bernoulli beams of two bending modes. Through simulating the system's postimpact dynamics response, the initial conditions are obtained from the impact model. Next, the initial velocities of base and joint are adjusted to minimize the velocity of the base after the capture according to generalized momentum conservation. After the capture, a proportional–derivative controller is designed to keep the robot system's stabilization. The simulation results show that joint angles of base and manipulators reach stable state quickly, and motions of the space robots also induce vibrating motions of the flexible manipulators.